The motive of a pregnant man in our knowledge - Popvasileva, Aleksandra (Traditiones (Ljubljana), 1999)
The appearance of the motif of a Pregnant Man as a folk fantasy expressed in the folk narrative tradition and in the myth, thematically is connected with the motive of a parthenogenesis, that is with a motive of a magic birth of a hero in folk stories, myths and legens. According of the knowledge of the author of this work, father gives a birth, contrary to parthenogenesis (with a meaning that a woman becomes pregnant in a magic way) did not raise a lot of interest in stories. It seems that this part of the pathogenesis in stories and scientific exploring is pushed back by the custom of kuvada. This custom has kept the interest of researchers - anthropologists and folklorists who include to kuvada stories and myths with the above mentioned motive
Keywords: ethnology; etnologija; ljudsko slovstvo; oral literature